2018
DOI: 10.1017/rdc.2018.90
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of dissolved organic14C-containing compounds by accelerator mass spectrometry in a corrosion experiment with irradiated steel

Abstract: Low- and intermediate-level (L/ILW) radioactive waste produced in Switzerland consists of large amounts of14C-containing irradiated steel.14C will be released during the anoxic corrosion of the steel in the cementitious near field of an L/ILW repository. In this study, a corrosion experiment with irradiated steel was carried out to determine the speciation of14C released during the corrosion process in conditions similar to those anticipated in the near field of a cement-based repository. The development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In the experiment of (Wieland et al 2017), 14 C-containing acetate, formate and lactate were identified and quantified (Cvetković et al 2018c). The proportions were as follows: acetate ~32%, formate ~40%, and lactate ~25%.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiment of (Wieland et al 2017), 14 C-containing acetate, formate and lactate were identified and quantified (Cvetković et al 2018c). The proportions were as follows: acetate ~32%, formate ~40%, and lactate ~25%.…”
Section: Resultsmentioning
confidence: 99%
“…An artificial cement pore water (ACW) with pH 12.5, used to simulate pore water conditions in the near field of a cement-based DGR and corresponding to a solution saturated w.r.t. Ca(OH) 2 , was prepared as reported elsewhere (Cvetković et al, 2018c).…”
Section: Solutions and Chemicalsmentioning
confidence: 99%
“…S1-1). Before starting the corrosion experiment, tests of the background 14 C activity and the concentrations of carbon compounds were carried out (Cvetković et al, 2018c) (S.I. S2).…”
Section: Reactormentioning
confidence: 99%
See 2 more Smart Citations